Pengaruh Model Pembelajaran Arias Terhadap Kemampuan Pemecahan Masalah Ips Ditinjau Dari Keterampilan Sosial Siswa Kelas V Sekolah Dasar Di Kecamatan Rancakalong Kabupaten Sumedang - Kosasih, Engkos; Suroyo, Suroyo; Suhartono, Suhartono (Universitas Pakuan, 2023)
THE EFFECT OF THE ARIAS LEARNING MODEL ON IPS PROBLEM-SOLVING ABILITY IN VIEW OF THE SOCIAL SKILLS OF 5TH-GRADE STUDENTS AT ELEMENTARY SCHOOL IN RANCAKALONG DISTRICT, SUMEDANG REGENCYThis experimental research has a 2x2 factorial design. The design of this study aims to examine the effect of applying the ARIAS learning model on social skills and problem-solving abilities in terms of students' social skills. Respondents in this study involved 38 students in class V at Pasirbenteng II Elementary School and 38 students at Citungku Elementary School, which were later divided into a control group and an experimental group. Sampling for the experimental group and the control group was carried out by means of a sampling technique, namely random group sampling (Cluster Random Sampling). Based on the analysis of research data and discussion, it was found that students using the ARIAS learning model were better than the learning outcomes of students treated with conventional learning models on social skills problem-solving abilities in terms of social skills.